89.9k views
4 votes
Which expressions are equivalent to -2y-8+4y ?-2(y+4)+4y4(-2+y)-2y

User Valignatev
by
4.9k points

1 Answer

2 votes

Given the expression :


-2y-8+4y

Simplify the given expression, the result will be :


-2y-8+4y=2y-8

Simplify the given options:


\begin{gathered} -2\mleft(y+4\mright)+4y \\ =-2y-8+4y \\ =2y-8 \end{gathered}

The second option is :


\begin{gathered} 4\mleft(-2+y\mright)-2y \\ =-8+4y-2y \\ =2y-8 \end{gathered}

so, the answer is :

The given expression is equivalent to the two options

User StrubT
by
6.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.